Evaporating hydrophilic and superhydrophobic droplets in electric fields - Gibbons, Michael; O'Shaughnessy, Seamus (My University, 2021)
Evaporating water droplets on a heated substrate are investigated in this work. Specifically, the influences of electric fields are studied in the context of the heat flux distribution beneath the droplets as well as the droplet mechanics and resulting shapes and forces. To facilitate a deeper understanding of the problem, both hydrophilic and superhydrophobic droplets are considered for an entire evaporation period with and without electric field effects. Both wetting scenarios show that the net radial directed electric force is directed inward, resulting in a compressive force which influences the droplet shape in such a way that it appears elongated. Conversely, the net vertically directed electric force is determined to be downwardly directed for hydrophilic droplets, pressing the droplet to the surface, whereas it is upwardly directed for the superhydrophobic droplets, representing a lifting force. With regard to the heat transfer to the droplets, only a pronounced electric field effect was observed for the superhydrophobic droplet. For all droplets, the contact line density, representing the ratio of the contact line perimeter to the total base area of the droplet, is determined to be a parameter that unifies the average heat flux from the heater to the droplets. This suggests that the heat transfer to the base of the droplet in the presence of an electric field is dominated by the electric fields influence, or lack thereof, on the contact line density.
PUBLISHED
Keywords: Droplet evaporation; Electric Field; Hydrophilic; Hydrophobic; Heat transfer; Contact line